IgE autoantibodies to nuclear antigens in patients with different connective tissue diseases: re-evaluation and novel findings - Kramer, Kathrin; Pecher, Ann-Christin; Henes, Jörg; Klein, Reinhild (Frontiers in Immunology, 2025)
IntroductionConnective tissue diseases (CTD) are characterised by the overproduction of multiple autoantibodies, especially antinuclear antibodies (ANA) of the IgG type. Meanwhile, also IgE autoantibodies have been described. The aim was therefore, to establish an ELISA for the demonstration of IgE autoantibodies to SSA/Ro, SSB/La, RNP proteins and dsDNA in sera from patients with systemic lupus erythematosus (SLE), Sjoegren’s syndrome (SS), and mixed connective tissue disease (MCTD) to investigate their frequency and clinical relevance.MethodsSerum samples from 110 patients with SLE, 118 patients with SS, 41 patients with MCTD, and 73 controls were analysed by ELISA for IgE autoantibodies against dsDNA, SSA/Ro52, and SSA/Ro60, SSB/La, and RNP proteins using recombinant antigens. Patients were assessed for different clinical manifestations.ResultsIn SLE and SS, IgE anti-SSA/Ro52-, -SSA/Ro60- and -SSB/La-antibodies showed a significantly higher reactivity than in controls. IgE anti-dsDNA-antibodies were present in 66% of SLE patients. In SLE, there was a correlation of IgE anti-dsDNA- and -anti-SSA/Ro52-antibodies with disease activity and cutaneous manifestation. Neither IgE anti-SSA/Ro- nor -anti-SSB/La-antibodies were associated with distinct clinical manifestations in SS. Also, anti-RNP-antibodies were found to be of the IgE type (up to 90% in MCTD and 70% in SLE). In MCTD, IgE anti-Sm/RNPB- and -anti-RNP68-antibodies correlated with pulmonary manifestations. IgE anti-dsDNA- but not the other IgE autoantibodies decreased under immunosuppressive therapy.ConclusionIgE anti-SSA/Ro-, -SSB/La-, -RNP-, and -dsDNA antibodies show a high frequency and specificity for the prevailing CTD. We confirmed an association of anti-dsDNA and anti-SSA/Ro52 antibodies with disease activity in SLE. In MCTD, there was an association of anti-Sm/RNP B and -RNP68 antibodies with pulmonary disorder.